Zero harm: worker involvement. The missing piece! - Bryson, Nigel (Bishop Auckland, 2011)
"Nigel has analysed the available literature on worker involvement in the last couple of years and the message is overwhelming. The higher level of worker involvement, the safer and healthier the workforce and the more efficient and profitable the organisation. Using this overwhelming research evidence, Nigel then goes on to analyse why the trade union health and safety representative has provided the most effective consultation model. He then goes on to demonstrate how these successful measures can be applied to any workplace, any size, unionised or non-unionised. At the heart of this book is a comprehensive review of workplace measures from successful organisations. Using his experience as one of the countries leading authorities on practical worker involvement he offers the reader a huge menu of ideas on preventing accidents an ill-health. Readers are the free to select the ones that may help them to improve their health, safety and business performance."